Rozumienie osoby ludzkiej w tradycjach chrześcijańskiego Wschodu i Zachodu a pojmowanie człowieka w antropologii medycznej - Leśniewski, Krzysztof (Studia Oecumenica, 2012)
Such issues as illness, treatment and health have been very important for every man and in every society. It is very difficult to define precisely these notions because they are based on the conception of human being. The anthropological presuppositions determine not only diagnosis of possible sources of illnesses but have also decisive influence on methods of treatment. This article has been an attempt of comparing philosophical and theological anthropology of Christian East and West with contemporary medical anthropology. The Author starts with questions concerning an identity of human being. Then there is presented the reductionist approach, which is characteristic for pluralistic philosophical thought on man. The central part of the article shows the timeless value and characteristics of the Christian concept of the person. The image of man in the contemporary medical anthropology has been shown in the fourth part of the elaboration. In the final part of the article it has been stated the question to what extent could Christian anthropology modify the generally accepted stereotypes of disease, treatment, and health. Author gives some arguments for a creation of a new field of science, namely Christian Medical Anthropology